Crosstalk Between Ethylene and Abscisic Acid During Changes in Soil Water Content Reveals a New Role for 1-Aminocyclopropane-1- Carboxylate in Coffee Anthesis Regulation - López, Marlon Enrique; Silva Santos, Iasminy; Marquez Gutiérrez, Robert; Jaramillo Mesa, Andrea; Cardon, Carlos Henrique; Espíndola Lima, Juliana Maria; Almeida Lima, André; Chalfun-Junior, Antonio (Frontiers in Plant Science, 2022)
Coffee (Coffea arabica L.) presents an asynchronous flowering regulated by endogenous and environmental stimulus, and anthesis occurs once plants are rehydrated after a period of water deficit. We evaluated the evolution of Abscisic Acid (ABA), ethylene, 1-aminocyclopropane-1-carboxylate (ACC) content, ACC oxidase (ACO) activity, and expression analysis of the Lysine Histidine Transporter 1 (LHT1) transporter, in roots, leaves and, flower buds from three coffee genotypes (C. arabica L. cv Oeiras, Acauã, and Semperflorens) cultivated under field conditions with two experiments. In a third field experiment, the effect of exogenous supply of ACC in coffee anthesis was evaluated. We found an increased ACC level, low ACO activity, decreased level of ethylene, and a decreased level of ABA in all tissues from the three coffee genotypes in the re-watering period just before anthesis, and high expression of the LHT1 in flower buds and leaves. Ethylene content and ACO activity decreased from rainy to dry period whereas ABA content increased. Higher number of opened and G6 stage flower buds were observed in the treatment with exogenous ACC. The results showed that the interaction of ABA-ACO-ethylene and intercellular ACC transport among leaves, buds, and roots in coffee favors an increased level of ACC that is most likely, involved as a modulator in coffee anthesis. This study provides evidence that ACC can play an important role independently of ethylene in the anthesis process in a perennial crop.